China and Europe's partnership for a more sustainable world : challenges and opportunities - Spigarelli, Francesca; Curran, Louise (Writer on environmental issues); Arteconi, Alessia (Emerald Group Publishing Limited, 2016)
This book gathers the main scientific outputs related to POREEN, a four-year project on partnering opportunities between Europe and China in the renewable energy and environmental industries, financed by the European Commission. It investigates the main challenges and opportunities related to Sino-European cooperation in the green sector with a focus on sustainable growth.The first part of the book outlines the characteristics of Chinese and European cooperation, from a policy, macro and microeconomic point of view. It examines the key elements of green policy developed so far, bilateral trade flows, as well as bilateral investment flows. The second part presents an overview and recommendations on what legal framework is necessary to boost integration between Europe and China. In addition, corporate social responsibility and firm related aspects are considered. The third part of the book focuses on engineering-related research activity. It highlights the state of the art of Europe-China cooperation in key areas such as low carbon buildings, mobility and transportation that may have a huge potential impact on bilateral cooperation between Europe and China in the years ahead.